Feedback Driven Fast Piezoelectric Micro-lens Actuator. (2016) - Michael, A.; Chen, S.S.; Kwok, C.Y.
Abstract: This paper studies the dynamic behavior of a piezoelectric micro-lens actuator driven by a feedback system. The feedback system consists of the actuator in the forward path and an optical displacement sensor and a 90 o phase shifter multiplied by a gain as feedback elements. The piezo-electric micro-lens actuator is fabricated and characterized for its dynamic performance by varying the feedback gain. The results show that the settling time and quality factor of the actuator are reduced by a factor of more than 100 and 10 dB, respectively when the gain is increased from 0 to 0.0134. The micro-lens actuator demonstrated switching time of 2.5ms at a resonance frequency of 750 Hz without affecting its static deflection characteristic. This is significantly fast in comparison to other reported switching times for micro-lens actuator.